KUALITAS UDARA EMISI GAS BUANG CEROBONG UNIT 3 & 4 DI PT. X - Rinata Fitria Sari; Natalina Natalina; Panisean Nasoetion (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This report discusses the air quality of flue gas emissions from Chimney Units 3 and 4 at PT. X. The study was conducted as part of an internship program aimed at evaluating emission testing methods, the compliance of test results with emission quality standards, and the potential impacts of air pollution. The testing methods applied refer to Government Regulation No. 22 of 2021 and the Ministry of Environment Regulation No. 15 of 2019. The test results show that the emission levels from both units remain below the established quality standards, although some parameters are approaching the threshold limits. Regular monitoring is conducted to ensure emissions remain within safe limits. It is expected that this report can provide useful information as a reference for air pollution control in the industrial sector.